An investigation of the relationship between government expenditure and revenue in a multicurrency economy: a case of Zimbabwe - Masere, Victoria; Kaja, Primrose (Journal of Economics and Sustainable Development, 2022)
This study investigated the nature of the relationship between government expenditure and revenue for Zimbabwe for the Multicurrency period using monthly time series data covering the period 2010 to 2012. Data was analysed using Granger (1969) causality tests and Cointergration analysis. The results from this study show that there is independence between government expenditure and government revenue hence providing evidence in support of the Institutional Seperation Hypothesis propounded by Wildasky (1988) and Baghestani and MacNown (1994). Hence policies to curb the budget deficit in Zimbabwe should be directed to other factors like economic growth which affect government expenditure and revenues.